Mechanism of International Legal Implementation for Human Security at the National Level - AVDEEV, Vadim Avdeevich; AVDEEVA, Olga Anatolievna; BYKOV, Anton Vitalyevich; ZNAMEROVSKIY, Evgeny Vasilyevich; AKSENOV, Alexey Nikolaevich; ZHIGALOV, Stanislav Valerievich (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020DO - 10.14505//jarle.v11.1(47).02, 2020)
The research analyzes current trends in ensuring personal security taking into account International Law. The priority position of the individual declared by the norms of international law is assessed differently by national legal systems. The interest of States in preserving the inviolability of fundamental human rights and freedoms implies the use of various mechanisms to achieve these goals. New trends in socio-economic development in the context of globalization predetermine the need to improve the national system for ensuring personal security taking into account international legal principles. Attention is focused on the state of human security and fundamental rights and freedoms declared by international and national law and guaranteed by the State. International normative and legal acts aimed at strategic directions of ensuring personal security are subject to analysis. The article notes the relationship between the transformation of socio-economic character and the state, structure, dynamics of crimes against the individual. Bringing the norms of national law into conformity with the norms, principles and provisions of international normative-legal acts of universal and regional character is recognized as one of the directions of ensuring personal security. The research is focused on the key areas of counteracting attacks on the person taking into account the novelization of modern criminal legislation and law enforcement activities. Close attention is paid to the development and implementation of organizational and practical measures to counteract crimes against the individual at federal and regional levels. The strategic directions developed and implemented at the national level to improve the effectiveness of activities related to ensuring human criminological safety are of applied importance. The conceptual directions of realization of the state policy on prevention, suppression and counteraction of violent crime against the person proposed in the article have practical and oriented value.